Pelatihan dan Pembuatan Banner pada Aplikasi Canva umtuk meningkatkan Kreativitas Desain Promosi Usaha Mikro Kecil dan Menengah Pondok Mapan Ibu Sundari di Desa Marga Bakti - Dinda Wahyuningsih; Darman Syafei; Merita Auli; Yunizir Djakfar; Indah Eliyana (CV. Aksara Global Akademia, 2025)
UMKM are crucial to the country's economy and job creation, and in order for them to compete, inventive innovations must be made. Research, creativity, and observation can all help achieve this. Promotion is a means of targeting prospective customers with information about a product to pique their interest. Canva is an online design platform that provides a wide range of tools for creating graphics, infographics, banners, presentations, resumes, posters, brochures, booklets, and much more. One of Canva's numerous benefits is its wide variety of eye-catching designs. This gives UMKM the freedom to select and improve the originality of their marketing material. According to observations, the proprietors have designed the products' packaging and branding, yet they lack the.